SIFO barometer 1967-1997 - Ekengren Oscarsson, Henrik; Swedish Institute of Public Opinion Research (University of Gothenburg, 1997)
Compilation of SIFO-surveys

Sammanställning av flera SIFO-undersökningar
SIFO-barometer 1967-1997
Keywords: POLITICAL ALLEGIANCE; POLITISK ANHÄNGARE; POLITICAL PARTIES; POLITISKA PARTIER; POLITICAL LEADERS; POLITISKA LEDARE; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap